A study of risk factors for ischemic heart disease in a village of Davanagere district: a case control study - G., Muhammed Muntazeem; G. K., Rathnaprabha; B. A., Varadaraja Rao; Kengal, Prakash (International Journal Of Community Medicine And Public Health, 2019)
Background: Ischemic heart disease is a multifactorial disease. Various behavioural risk factors like smoking, physical inactivity, unhealthy diet and alcohol are known to be important risk factors for IHD. Methods: A case control study was conducted at Kerebilachi village, Davanagere. 40 known cases of Ischemic heart diseases and 80 controls were studied. The association of various risk factors with IHD was assessed. Data was entered in the Microsoft excel and analysed using SPSS v20. Results: Smoking, diabetes, hypertension, physical inactivity and obesity were important risk factors considered in this study. Significant association was observed with smoking (OR 6.15, CI: 2.646 -14.289.), diabetes (OR 5.28, CI: 1.80-18.54), hypertension (OR.35, CI: 0.12-1.01) and obesity (OR 0.74, CI: 1.06—8.23). Conclusions: This study reinforces the importance of risk factors which are modifiable and preventable.